PEMANFAATAN RPTRA SEBAGAI UPAYA EDUKASI PENGEMBANGAN PERTANIAN PERKOTAAN DI KELURAHAN PASEBAN KECAMATAN SENEN JAKARTA PUSAT - Rayuna Handawati; Adhira Riza Muqtadir; Algiyan Toni; Lyzia Nabilla; Ragil Bunga Setianingsih; Rantian Virta Eka Pratiwi; Shaquila Shaquila (Geography Education Study Program, Universitas Samudra, 2022)
Change of land use has become a regional issue, although on the one hand it can optimize resources use, but on the other hand it also reduce environmental capacity in maintaining food production. Until 2013, the number of new Green-Open Area (RTH) in Jakarta reached 9% of the total area. This number is still far from the minimum value that has been set (30%). Te purpose of this research is to provide ideas in the development of urban agriculture to overcome the limitations of urban land by maximizing the use of Child Friendly Integrated Public Space (RPTRA) An-Nur as a means of urban farming education, providing input for RPTRA An-Nur managers and local communities as the innovation in the development of urban agricultural system. The research method used in this study is a descriptive method with qualitative approach. In this study, the population is all the RTH of Sub-Disctrict Paseban, District Senen, in Central Jakarta, while the sample in this study was RPTRA An-Nur.